2018
DOI: 10.1001/jamaneurol.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regulatory T Lymphocytes in Amyotrophic Lateral Sclerosis

Abstract: 14. Liguori C, Mercuri NB, Izzi F, et al. Obstructive sleep apnea is associated with early but possibly modifiable Alzheimer's disease biomarkers changes. Sleep. 2017;40(5):zsx011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
4
11
0
Order By: Relevance
“…This is in line with the recognized dual role that histamine plays for instance in microglia, that is, detrimental under healthy conditions and beneficial within inflammatory environments . It might also be explained by histaminergic drugs acting on cell types that per se possess dual roles in ALS pathogenesis, for instance microglia and immune cells preventing disease progression at early stages while inducing pathogenic responses at later stages …”
Section: Discussionsupporting
confidence: 68%
“…This is in line with the recognized dual role that histamine plays for instance in microglia, that is, detrimental under healthy conditions and beneficial within inflammatory environments . It might also be explained by histaminergic drugs acting on cell types that per se possess dual roles in ALS pathogenesis, for instance microglia and immune cells preventing disease progression at early stages while inducing pathogenic responses at later stages …”
Section: Discussionsupporting
confidence: 68%
“…Tregs maintain homeostasis by inhibiting effector T-cell proliferation and cytokine production, shutting down an overactive immune response. In accord with the pro-inflammatory state reported in peripheral blood from ALS patients, fewer Tregs have also been observed in patient and rodent models of ALS [ 13 , 14 , 93 , 136 ]. Treg levels were found to correlate with disease progression rates in mutant SOD1 mice, and passive transfer of Tregs suppressed neuroinflammation and prolonged survival in these animals [ 169 ].…”
Section: Introductionsupporting
confidence: 57%
“…Our study did not investigate the mechanisms involved in clinical improvement. The suggested role of natural killer cells [ 44 ] and regulatory T cells [ 45 , 46 ] is in line with the mechanism of action of MSC described by other authors [ 47 50 ]. Some studies indicated that human neural stem cells transplanted into a spinal cord in patients with ALS differentiated into neurons which were still detected 2.5 years after administration; however, it is not known whether the same happens after administration of MSC [ 51 ].…”
Section: Discussionsupporting
confidence: 76%